Answer:
x =
, x = 1
Explanation:
(a)
= x + 7 ( multiply both sides by 2 to clear the fraction )
4x - 1 = 2x + 14 ( subtract 2x from both sides )
2x - 1 = 14 ( add 1 to both sides )
2x = 15 ( divide both sides by 2 )
x =
![(15)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/etypoi8sj65nw7ym2ve6mm9may8m2wlgfi.png)
(b)
3x + 2 =
( multiply both sides by 3 to clear the fraction )
9x + 6 = 2x + 13 ( subtract 2x from both sides )
7x + 6 = 13 ( subtract 6 from both sides )
7x = 7 ( divide both sides by 7 )
x = 1